The Impact of Employee Creativity on Employee Performance Mediated by Innovative Work Behavior Among Millennial Employees in Pasuruan, East Java - Achdian, miftah; Setiawan, Nurcholis (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This study aims to examine the effect of employee creativity on employee performance mediated by innovative work behavior in millennial employees in Pasuruan, East Java. Millennials, known for their tendency to be more creative and innovative, face challenges in developing creativity in a workplace that is still strictly structured. This study uses quantitative methods with data collection through questionnaires distributed to millennial employees in various companies in Pasuruan. The results showed that employee creativity has a significant positive effect on employee performance (path coefficient of 1.977, p = 0.048). In addition, employee creativity also has a significant effect on innovative work behavior (path coefficient of 25.523, p = 0.000), which in turn has a significant positive effect on employee performance (path coefficient of 5.629, p = 0.000). Innovative work behavior was shown to mediate the effect of creativity on employee performance (path coefficient of 5.549, p = 0.000). Thus, this study concludes that increasing employee creativity can significantly improve employee performance, and this effect is amplified through innovative work behavior. These results provide practical implications for companies to encourage creativity and innovation in the workplace as a strategy to improve employee performance, especially the millennial generation. Keywords: Employee Creativity, Employee Performance, Innovative Work Behavior